Implementation of Wireless Sensor Network on Fire Early Warning System Using GSM Communication - Satria, Dedi; Safrina Dewi, Sri; ., Zulfan; Yusibani, Elin; Sugiyanto, Didik (International Journal of Engineering and Technology, 2019)
Wireless Sensor Network (WSN) is a concept in which the information delivery system from a sensor from a workstation or node to the center of the information system through a wireless network either in the form of a computer network or GSM network. The use of Wireless Sensor Network (WSN) has been widely applied in various fields of military, health and disaster. Therefore, this article discusses how to implement the Wireless Sensor Network (WSN) by using GSM as a communication medium for fire early warning systems. The flood early warning system is built into 2 separate systems namely a client system consisting of fire sensors, smoke sensors, microcontrollers and GSM modules. Then the server system is built using Apache Web Server, PHP Engine, mySQL and Gammu. This study produced a prototype of a fire early warning system that has successfully sent fire data in the form of web and SMS based information display.